Impact of blood pressure on clinical outcome of acute ischemic stroke over two months in a tertiary care hospital of Bangladesh (Bangladesh Critical Care Journal, 2022)
Background: Stroke is a familiar medical emergency and is one of the notable causes of death in Bangladesh.Objective: To determine the impact of systolic blood pressure (SBP) on outcomes of the patient with acute ischemic stroke. Materials and methods: This prospective observational study was conducted in Dhaka Medical College Hospital from August 2015 to February 2016 with 100 participants admitted to medicine ward with ischemic stroke. SBP was measured and Modified Rankin’s scale (MRs) was calculated. Outcomes at discharge and in 2nd month were evaluated by MRs and observed in relation to SBP.Results: 58% were found to be dependency group, followed by 27% and 15% were in good outcome group and dead respectively within 7 days. 37% were found to be in good outcome group in the 2nd month. 31% were in dependency group and 32% died at the end of 2 months. The mean SBP was 158.40 mmHg ranging from 100 mmHg to 230 mmHg. Mean SBP of good outcome at discharge and 2nd month were 144.63 (±21.48) and 145.68 (±22.05) respectively. Mean SBP was higher (p-value